A plastidial retrograde signal potentiates biosynthesis of systemic stress response activators. Issue 4 (24th December 2021) - Zeng, Liping; Wang, Jin‐Zheng; He, Xiang; Ke, Haiyan; Lemos, Mark; Gray, William M.; Dehesh, Katayoon
Summary: Plants employ an array of intricate and hierarchical signaling cascades to perceive and transduce informational cues to synchronize and tailor adaptive responses. Systemic stress response (SSR) is a recognized complex signaling and response network quintessential to plant's local and distal responses to environmental triggers; however, the identity of the initiating signals has remained fragmented. Here, we show that both biotic (aphids and viral pathogens) and abiotic (high light and wounding) stresses induce accumulation of the plastidial‐retrograde‐signaling metabolite methylerythritol cyclodiphosphate (MEcPP), leading to reduction of the phytohormone auxin and the subsequent decreased expression of the phosphatase PP2C.D1. This enables phosphorylation of mitogen‐activated protein kinases 3/6 and the consequential induction of the downstream events ultimately, resulting in biosynthesis of the two SSR priming metabolites pipecolic acid and N ‐hydroxy‐pipecolic acid. This work identifies plastids as a major initiation site, and the plastidial retrograde signal MEcPP as an initiator of a multicomponent signaling cascade potentiating the biosynthesis of SSR activators, in response to biotic and abiotic triggers.